Evaluation of Techniques for the Presentation of Laboratory Data: Support of Pattern Recognition - Hoeke, J. O. O.; Bonke, B.; van Strik, R.; Gelsema, E. S. (Methods of Information in Medicine, 2000)
Two tabular and two graphical techniques for the presentation of laboratory test results were compared in a reaction-time experiment with 22 volunteers. The experimental setup was designed to determine whether one or more of the presentation techniques facilitated the recognition of four predefined combinations of abnormal test results. Using a conventional, tabular presentation technique as a reference, faster median response times were obtained with each of the other three presentation techniques, irrespective of pattern. The effect on accuracy was less clear, possibly due to the small number of errors made.
Keywords: Laboratory Test Results; Color Coding; Graphical Representation; Evaluation